Investigation on Sb distribution for InSb/InAs sub-monolayer heterostructure using TEM techniques. (11th October 2019) - Khan, Atif A; Herrera, M; Fernández-Delgado, N; Reyes, D F; Pizarro, J; Repiso, E; Krier, A; Molina, S I
Abstract: InSb/InAs sub-monolayer (SML) nanostructures such as SML quantum dots offer sharper emission spectra, a better modal gain and a larger modulation bandwidth compared to its Stranski–Krastanov counterpart. In this work, the Sb distribution of SML InSb layers grown by migration enhanced epitaxy has been analyzed by transmission electron microscopy (TEM) techniques. The analysis of the material by diffraction contrast in 002 dark field conditions and by atomic column resolved high angle annular dark field-scanning TEM reveal the presence of a low Sb content InSbAs continuous layer with scarce Sb-rich InSbAs agglomerates. The intensity profiles obtained by both techniques point to Sb segregation during growth. This segregation has been quantified using the Muraki segregation model obtaining a high segregation coefficient R of 0.81 towards the growth direction. The formation of a continuous InSbAs wetting layer as a result of a SML deposition of Sb on the InAs surface is discussed.